Sílica gel organofuncionalizada com 4-amino-5-(4-piridil) 4H-1,2,4-triazol-3-tiol (aptt): Propriedades adsortivas e eletroanalíticas - Magossi, Maiara de Souza [UNESP] (2015)
In the present work, 3-chloropropyl silica gel (SG) was prepared and organofunctionalized with 4-amino-5-(4-pyridyl)-4H-1,2,4-triazole-3-thiol (APTT), and the material obtained of the functionalization was described as SGAPTT. The material obtained was characterized by different experimental techniques such as spectroscopy in the infrared (FTIR), energy dispersive X-ray (EDX), scanning electron microscopy (SEM). Was performed to analyze the surface area and porosity for the precursor and the SG SGAPTT product. After the structural and morphological characterization of metal ion adsorption studies were performed (Cu 2+ ) to SGAPTT in different media, such as water, ethanol 42% and 99% ethanol at different temperatures, such as 25, 35 and 45 ° C. Determined the adsorption equilibrium time, where for all media studied was on average 40 minutes. Then, we determined the adsorption capacity (N f max ) through isotherms with different molar concentrations of Cu 2+ ions, the values obtained for the N f max aqueous solution was 22.0 × 10 -5, 24, 0 × 10 -5 and 28.0 x 10 -5 mol g -1 for the temperatures 25, 35 and 45 ° C respectively. For the 42% ethanolic medium N f max values were 31.4 × 10 -5, 39.4 × 10 -5 and 41.2 x 10 -5 mol g -1 and 99% ethanolic medium values N f max were 47.17 × 10 -5, 50.3 × 10 -5 and 56.8 x 10 -5 mol g -1 at temperatures of 25, 35 and 45 ° C respectively. The N f values increased according to the following order of solvents: water <42% ethanol <99% ethanol. The Langmuir model was the most appropriate to describe the adsorption data. The thermodynamic parameters ΔG, ΔH and ΔS were evaluated for SGAPTT material, and it was observed that the adsorption capacity increased with increasing temperature, indicating an endothermic process. The values of (ΔG <0) indicate that the adsorption process is spontaneous and positive values of entropy indicate that there is an increase ...